Pharmacological activation of the amygdala, but not single prolonged footshock-induced acute stress, interferes with cue-induced motivation toward food rewards in rats - Lai, Chien-Wen; Chang, Chun-hui (Frontiers in Behavioral Neuroscience, 2023)
In the face of threats, animals adapt their behaviors to cope with the situation. Under such circumstances, irrelevant behaviors are usually suppressed. In this study, we examined whether food-seeking motivation would decrease under activation of the amygdala, an important nucleus in the regulation of stress response in the central nervous system, or after a physical acute stress session. In Experiment 1, we pharmacologically activated the basolateral nucleus (BLA) or the central nucleus of the amygdala (CeA) before a cue-induced reinstatement test in rats. Our results showed that activation of the BLA or the CeA abolished cue-induced motivation toward food rewards, while locomotor activity and free food intake were not affected. In Experiments 2 and 3, we further assessed anxiety and despair levels, as well as cue-induced reinstatement, after a single prolonged footshock-induced acute stress in rats. Behaviorally, acute stress did not affect anxiety level, despair level, or cue-induced motivation toward food rewards. Physiologically, there was no difference in cellular activities of the amygdala immediately after acute stress. To conclude, our results suggested that pharmacological activation of the amygdala decreased cue-induced motivation toward food reward. However, physiological acute stress did not immediately interfere with the negative emotions, motivation, or amygdala activities of the animals.